Integrating Robotic Technology Into Resident Training: Challenges and Recommendations From the Front Lines. (October 2019) - Green, Courtney A.; Mahuron, Kelly M.; Harris, Hobart W.; O'Sullivan, Patricia S.
Abstract : Purpose: To develop recommendations for improving the integration of robotic technology into today's apprentice-based resident training. Method: During a national meeting in 2017, 24 robotic surgeons were interviewed about their experiences integrating robotic technology into resident training. Qualitative thematic analysis of interview notes and recordings revealed themes related to challenges and recommendations. Results: Four themes emerged, each corresponding to a general recommendation for integrating robotic technology into training. The first, surgical techniques versus tools, contrasts faculty's sequential mastery—surgical techniques first, then the robotic tool—with residents' simultaneous learning. The recommendation is to create separate learning opportunities for focused skill acquisition. The second theme, timing of exposure to the robotic tool, describes trainees' initial focus on tool use for basic surgical steps. The recommendation is to increase access to basic robotic cases. The third theme covers the relationship of laparoscopic and robotic surgery. The recommendation is to emphasize similar and dissimilar features during all minimally invasive surgical cases. The fourth theme, use of the dual console (which enables two consoles to operate the robot, the primary determines the secondary's functionality), highlights the unique teaching opportunities this console creates. The recommendation is for surgeons to give verbal guidance so residents completely understand surgical techniques. Conclusions: Surgical educators should consider technique versus tool, timing of exposure to the tool, overlapping and varying features of robotic and laparoscopic surgery, and use of the dual console as they develop curricula to ensure thorough acquisition and synthesis of all elements of robotic surgery. Abstract : Supplemental Digital Content is available in the text.